Factors Associated with Perpetration of Physical Intimate Partner Violence among College Students: Russia and Lithuania. Issue 2 (1st February 2017) - Kamimura, Akiko; Chernenko, Alla; Nourian, Maziar M.; Assasnik, Nushean; Franchek-Roa, Kathy
ABSTRACT: This study examined factors associated with physical IPV perpetration in Russia and Lithuania. The data from the International Dating Violence Study 2001–2006 were analyzed ( N = 818). Male and female perpetrators as compared to non-perpetrators of physical IPV have a higher prevalence of being perpetrators of other forms of IPV. Perpetrators of physical IPV as compared to non-perpetrators are more likely to have been victims of IPV. Male and female 'intimate terrorist' perpetrators exhibit different characteristics. Factors associated with IPV are different between male and female perpetrators. Interventions should focus on victimization and perpetration.